2002
DOI: 10.1093/molehr/8.4.399
|View full text |Cite
|
Sign up to set email alerts
|

Use of cDNA arrays to generate differential expression profiles for inflammatory genes in human gestational membranes delivered at term and preterm

Abstract: Inflammatory processes are implicated in preterm labour (PTL). To identify potential novel markers for PTL, we have used commercial cDNA arrays to generate profiles of differential expression of inflammation-associated genes in gestational membranes with term and PTL. RNA for cDNA probe synthesis was isolated from reflected human amnion and choriodecidua membranes delivered following Caesarean section at term before the onset of labour (TNL, n = 4), spontaneous labour at term (TSL, n = 4), and PTL with and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
100
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 76 publications
3
100
0
Order By: Relevance
“…Functional genomics has arrived at the study of parturition in different species: mice (Bethin et al 2003, Salomonis et al 2005; rats (Girotti & Zingg 2003) and humans (Chan et al 2002, Marvin et al 2002a, 2002b, Tashima et al 2002, Bethin et al 2003, Charpigny et al 2003, Keelan et al 2003, Esplin et al 2005, Havelock et al 2005. Also in different tissues: myometrium (Aguan et al 2000, Chan et al 2002, Bethin et al 2003, Charpigny et al 2003, Esplin et al 2005, Havelock et al 2005, Salomonis et al 2005; primary cultures of human myometrial cells ; fetal membranes (Muhle et al 2001, Chen et al 2002, Marvin et al 2002a, 2002b, Tashima et al 2002, Keelan et al 2003 and trophoblasts (Chen et al 2002, Kato et al 2002.…”
Section: Functional Genomic Studies During Pregnancymentioning
confidence: 99%
See 2 more Smart Citations
“…Functional genomics has arrived at the study of parturition in different species: mice (Bethin et al 2003, Salomonis et al 2005; rats (Girotti & Zingg 2003) and humans (Chan et al 2002, Marvin et al 2002a, 2002b, Tashima et al 2002, Bethin et al 2003, Charpigny et al 2003, Keelan et al 2003, Esplin et al 2005, Havelock et al 2005. Also in different tissues: myometrium (Aguan et al 2000, Chan et al 2002, Bethin et al 2003, Charpigny et al 2003, Esplin et al 2005, Havelock et al 2005, Salomonis et al 2005; primary cultures of human myometrial cells ; fetal membranes (Muhle et al 2001, Chen et al 2002, Marvin et al 2002a, 2002b, Tashima et al 2002, Keelan et al 2003 and trophoblasts (Chen et al 2002, Kato et al 2002.…”
Section: Functional Genomic Studies During Pregnancymentioning
confidence: 99%
“…Also in different tissues: myometrium (Aguan et al 2000, Chan et al 2002, Bethin et al 2003, Charpigny et al 2003, Esplin et al 2005, Havelock et al 2005, Salomonis et al 2005; primary cultures of human myometrial cells ; fetal membranes (Muhle et al 2001, Chen et al 2002, Marvin et al 2002a, 2002b, Tashima et al 2002, Keelan et al 2003 and trophoblasts (Chen et al 2002, Kato et al 2002. Various methodologies have been used: suppression subtractive hybridization (SSH) (Chan et al 2002) or microarrays for most of the previous cited studies.…”
Section: Functional Genomic Studies During Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation is now widely accepted to be a key feature of human labour. Microarray and suppression subtractive hybridization studies have demonstrated the up-regulation of a large panel of pro-inflammatory genes in both fetal membranes (Marvin et al 2002, Bethin et al 2003 and myometrium (Chan et al 2002, Charpigny et al 2003 with labour onset. Extensive work over the last two decades has implicated cytokines and prostaglandins in the parturition process.…”
Section: Introductionmentioning
confidence: 99%
“…This concept opens up new possibilities to relate stress to the immune system, possibly leading to the risk of infection, (and thus increased risk of premature delivery), with or without associated polymorphism, depending on the genetic susceptibility to inflammation, the inflammation present before and during pregnancy and the allostatic overload of women. Allostatic overload is defined as the wear of the neuro-endocrine systems, for an extreme activity or too low, in response to the tensions and the need to adapt [4]. The allostatic overload quantifies the physiological and neuroendocrinological fluctuating changes of the organism, produced by the acute and chronic psychosocial stress, over time.…”
Section: Interaction Between Maternal Stress and Preterm Deliverymentioning
confidence: 99%